Evaluasi Pelaksanaan Program Character Building Training di Universitas Islam Negeri Alauddin Makassar - Mania, Sitti; Hasaruddin, Hasaruddin (Sekolah Tinggi Agama Islam (STAIN) Curup, 2018)
This research is aimed to: 1) find out the objective condition of supporting elements of Character Building Training Program in State Islamic University of Alauddin Makassar at the antecedent phase, 2) look over the efectivity of the program implementation at the transaction phase, and 3) identify the character of students as the outcome of CBT Program. This formative evaluation research applies qualitative research particulary countenance stake. The data are collected by observation, questionnaire, interview, and documentation. The data are analyzed by domain analysis technique, tacsonomy, and componential technique, based on evaluation phase and applied together with data collecting. This research points out that antecedents phase is on the high category and transaction and outcomes phase are on moderat category.